Multimodalitas Wacana Kritis Keagamaan Dalam Komik Aji Prasetyo - Alfiandi Eka Kusuma; Gusnita Linda (Universitas Bumigora, 2022)
Comics as a popular visual communication medium are potential to carry sensitive discourses flexibly and freely. The nature of comics that involves the reader in filling out messages, as well as forms of multimodal communication through images and texts also support that potention. Serious, sensitive, and critical topics, such as religion, are often found in comics. One of the actual comics with a critical religious theme is the comic by Aji Prasetyo. This journal will analyze critical religiousity discourse in Aji Prasetyo's comics through a multimodal approach. The analysis was using the analysis method by Kress and Van Leeuwen, with the help of McCloud's comic theory. The results show that the interweaving of signs in visual mode and verbal mode in comics is related to each other to form discourse. Signs in the visual mode in the form of icons play an important role as a representation of characters and ideas. While in verbal mode, the caption dominates the comic as a representation of the author's critical opinion. The interweaving of signs in this fashion hybridity constructs a critical discourse about the contradictions of religious expression between formalism and substantialism.